Nanostructuring of Anodic Copper Oxides in Fluoride-Containing Ethylene Glycol Media - Sanchez-Poblete, J (Elsevier B.V., 2017)
We demonstrate that the anodization of copper in alkaline water/ethylene glycol media containing fluoride ions generates nanostructured copper oxide films. By modifying the anodization conditions (fluoride and OH– concentrations, applied voltage and anodization time), nanofibrillar Cu2O as well as highly rough nanofibrillar network or nanoporous mixed Cu2O/CuO films are obtained. Raman and X-ray Photoemission Spectroscopy (XPS) results indicate that in fluoride presence, Cu(I) oxide is obtained when anodization takes place applying low voltages at a relatively low OH– concentration. In comparison, the subsequent oxidation to obtain Cu(II) species (CuO and Cu(OH)2) is promoted by increasing the OH– contents. According to the present results, an oxidation reaction scheme is proposed in order to gain a deeper understanding in the preparation of controlled nanostructured copper oxide films. © 2017 Elsevier B.V.